2001
DOI: 10.1046/j.1440-1681.2001.03429.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Of Serum Tumour Necrosis Factor‐α With Serum Low‐Density Lipoprotein–Cholesterol And Blood Pressure In Apparently Healthy Japanese Women

Abstract: 1. The pro-inflammatory cytokine tumour necrosis factor (TNF)-alpha is considered to be involved in the development of atherosclerosis by inducing local inflammatory responses in the vascular wall. Because TNF-alpha is also known to affect lipid and glucose metabolism, the association between the circulating concentration of TNF-alpha and atherogenic risk factors was examined in 82 apparently healthy Japanese women (aged 19-69 years; mean age 48.5 years). 2. The mean (+/-SD) serum TNF-alpha concentration was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 40 publications
4
26
0
2
Order By: Relevance
“…30 Therefore, IL-6 may result in elevated BP by inducing endothelial dysfunction and increasing peripheral vascular resistance. 31,32 Some reports of studies in human subjects have shown a significant association between TNF-a and elevated BP, 11,12,21 but others have failed to show such an association. 13,14 Unfortunately, none of these studies has been designed to test this hypothesis and all have failed to control for other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Therefore, IL-6 may result in elevated BP by inducing endothelial dysfunction and increasing peripheral vascular resistance. 31,32 Some reports of studies in human subjects have shown a significant association between TNF-a and elevated BP, 11,12,21 but others have failed to show such an association. 13,14 Unfortunately, none of these studies has been designed to test this hypothesis and all have failed to control for other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] On the other hand, results from studies on the association between interleukin-6 (IL-6) and HBP have been contradictory. 9,10 Similarly, some studies in human subjects have shown a positive association between tumour necrosis factor alpha (TNF-a) level and HBP, 11,12 but others have not. 13,14 However, most of these studies were not designed to test the association between inflammation markers and HBP and have failed to control for other risk factors for HBP and for other inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…31 Another study showed that TNF-α 308G was associated with increased risk of hypertension. 32 Ito et al, 33 investigated the correlation of TNF-α with atherogenic risk factors in women. They observed that the serum level of TNF-α was significant related with obesity, hyperlipidemia and hypertension.…”
Section: Tnf-α Gene (-308 G→a and Lt-alpha +252 A→g) As Risk Factors mentioning
confidence: 99%
“…44 Moreover, TNF-a plays a fundamental role in inducing IEDD, 37 a condition that seems to play a role in the pathogenesis of essential hypertension and that is also present in offspring of hypertensive patients. 11,10 Some studies in human subjects (Table 3) have shown a positive association between TNF-a level and HBP, 16,33,34 while others have not. 27,29 However, these studies have failed to control for other risk factors for HBP.…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…IL-6 and TNF-a levels have also been associated to HBP in several epidemiologic studies. 16,[27][28][29][30][31][32][33][34] IL-6 is a 26-kDa cytokine, produced by different cells, including monocytes, lymphocytes, and endothelial cells. IL-6 stimulates the synthesis of many acute-phase reaction proteins, including CRP, serum amyloid A, and fibrinogen.…”
Section: Epidemiologic Evidencementioning
confidence: 99%